Lingkungan Taman Kanak-Kanak sadar sampah organik dan anorganik di Tamalanrea Makassar - Muhammad Abdy; Syafruddin Side; Wahidah Sanusi (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This Community Partnership Program (PKM) conducted at Bunga Asya Kindergarten in Makassar. The purposes of this activity are to increase a) knowledge and skills of parents and teachers of kindergarten (partners) on the importance of hygiene and health; b) partners' understanding on organic and inorganic waste in schools; and c) partners' knowledge and skills in understanding and utilizing organic waste. The identified problems are a) insufficient knowledge and skills about hygiene and health; b) insufficient knowledge and skills regarding organic and inorganic waste; and c) insufficient knowledge and skills in utilizing organic and inorganic waste. The methods used is this program are training, mentoring, and discussion between team and partners. This program involved 30 participants which then evaluation and monitoring are carried out periodically for 3 months. The results of this program showed that 1) skills and knowledge of the partners are improved; 2) partner groups were able to utilize organic and inorganic waste, and 3) publication in mass media or journals with ISSN.